A maritime navigation display that provides visual feedback to improve conning officers' ship-handling during low visibility environments. - Evanoff TV; Krebs WK (Ergonomics, 2002)
Navigating a ship at night in close proximity to another vessel is a dangerous task. To improve conning officers' night time ship-handling performance, a visual navigation display is proposed that is mounted on the stern of the aircraft carrier that will help shipboard conning officers manoeuvre in a battle group formation. To test the effectiveness of the visual navigation display, the Nimitz-class aircraft and plane guard vessel, a Ticonderoga-class cruiser, were modelled in a virtual environment. A navigation display condition had significantly fewer navigational positional errors than a non-navigation display condition. The navigation display provided immediate feedback as to whether the aircraft carrier had changed bearing or speed, thus enabling the operator to initiate the appropriate input to maintain station astern of the carrier. Actual or potential applications of this research include the deployment of a maritime navigation display to assist conning officers' ship handling.